The Night Witches - Ennis, Garth (Dead Reckoning, 2019)
"As the German Army smashes deep into Soviet Russia and the defenders of the Motherland retreat in disarray, a new squadron arrives at a Russian forward airbase. Like all night bomber units, they will risk fiery death flying obsolete biplanes against the invader--but unlike the rest, these pilots and navigators are women. In the lethal skies above the Eastern front, they will become a legend--known to friend and foe alike as the Night Witches. With casualties mounting and the conflict devouring more and more of her comrades, Lieutenant Anna Kharkova quickly grows from a naive teenager to a hardened combat veteran. The Nazi foe is bad enough, but the terrifying power of her country's secret police makes death in battle almost preferable. Badly wounded and exiled from her own people, Anna begins an odyssey that will take her from the killing fields of World War II to the horrific Soviet punishment camps--and at the top of the world, high above the freezing Arctic Ocean, the Night Witch finds she has one last card to play."--